Accuracy of clinical indicators of Nursing diagnoses hyperthermia and hypothermia in newborns - Braga, Fernanda Cavalcante; Santos, Alessandro Rodrigues Costa; Castro, Natália Barreto de; Nunes, Marília Mendes; Lopes, Marcos Venícios de Oliveira; Silva, Viviane Martins da (Rev Rene, 2014)
This study aimed at determining the accuracy of clinical indicators of Nursing diagnoses hyperthermia and hypothermia in newborns. This was a cross-sectional study carried out in 2013 in a reference maternity in Fortaleza, CE, Brazil with 46 newborns. Data collection was performed using an instrument developed based on the clinical indicators of these diagnoses, both from NANDA International. Diagnostician nurses were selected to perform diagnostic inference. Irritability, restlessness, bradycardia, pallor, jaundice, tachycardia, slow capillary refill and peripheral vasoconstriction were specific clinical indicators for hypothermia and body temperature below the normal range was the only sensitive indicator. Tachypnea, vasodilation and apnea were specific to hyperthermia however sensitive indicators were not found. We believed that the findings of this research can contribute to proper and fast inference of hypothermia and hyperthermia in newborns.